Perceptions of facilitators, barriers and solutions when preparing to implement a home visiting program in Sweden: a mixed-methods study - Lundgren, Julie S.; Nilses, Åsa; Eckerdal, Ebba-Lisa; Bernhardsson, Susanne (Frontiers in Health Services, 2024)
Background: Although there is growing awareness that early childhood development programs are important for a sustainable society, there is a knowledge gap about how to implement such programs. Successful implementation requires attention to implementation drivers (competency, organization, and leadership) during all phases of the implementation. The purpose of this study was to describe cross-sectoral operational workgroups' perceptions of facilitators, barriers and solutions related to implementation drivers in the preparation phase of implementing an evidence-based early childhood home visiting program. Methods: Quantitative and qualitative data were collected from twenty-four participants, divided into 5 groups, during implementation planning workshops. The workshops were guided by a structured method informed by the principles of Motivational Interviewing and within a framework of implementation drivers. Groups sorted cards with statements representing implementation drivers according to perceptions of facilitators and barriers, and percentages were calculated for each type of implementation determinant, for each type of driver. The groups discussed their card sorting and wrote action plans to address barriers, yielding documentation that was analyzed using deductive qualitative content analysis. Results: A mixed-methods analysis resulted identification of facilitators, barriers, unknowns and solutions in two to three subcategories under each main category of implementation driver. A competent and confident workforce, and enthusiasm and commitment were key facilitators. Key barriers were unclear roles and responsibilities, and insufficient articulation of local vision and goals. Many factors were described as yet unknown. Specific solutions were generated to support the implementation. Conclusions: Our study furthers the scientific understanding of how to take evidence-based early childhood programs from research to practice within an implementation drivers framework. Facilitators, barriers and solutions in key areas during the preparation phase were identified with the help of a novel tool. The results provide useful knowledge for decision makers and organizations preparing similar initiatives in communities striving to attain sustainable development goals.